Determination of corypalmine in mouse blood by UPLC–MS/MS and its application to a pharmacokinetic study. (10th May 2018) - Wu, Haiya; Yan, Qizhi; Fan, Zhehua; Huang, Miaoling; He, Jiamin; Ma, Jianshe; Wang, Xianqin
Abstract: In this work, a selective and sensitive ultra‐performance liquid chromatography tandem mass spectrometry method was established and validated for determination of corypalmine in mouse blood after oral or intravenous administration. A UPLC BEH C18 column was used to separate corypalmine and berberrubine (internal standard) at 40°C. The mobile phase was composed of acetonitrile and 10 mmol/L ammonium acetate (containing 0.1% formic acid) at a flow rate of 0.4 mL/min, and the total run time was 4.0 min. Electrospray ionization in positive ion mode was applied; target fragment ions m / z 342.2 → 178.0 for corypalmine and m / z 322.1 → 307.0 for berberrubine were identified with multiple reaction monitoring mode. The linear range was 1–1000 ng/mL ( r  > 0.995) and the lower limit of quantification for corypalmine in plasma was 1.0 ng/mL. The intra‐ and inter‐day precisions were both <14%. The range of accuracy in this method was 97.5–109.0%. Mean recovery was >69.6%, and the matrix effect was 96.8–107.6%. Based on its high sensitivity, specificity and reliability, this method was successfully applied to study the pharmacokinetic parameters of corypalmine in mouse by oral and intravenous administration, and finally, the bioavailability of corypalmine was identified at 4.6%.